(untitled) (Journal of Rashid Latif Medical College, 2022)
Objective: Two heptad repeat regions are present at envelop of HIV. It isassumed that this region plays an important role in the entry of viral genomeinto human cell. Present study was conducted for isolation andcharacterization of the HR region of env gene in samples of HIV taken fromPakistani patients. Methods: QIAamp MinElute® Spin Kit was used toisolate viral RNA and RT-PCR was used to amplify the specific regions fromsynthesized cDNA; and gel electrophoresis was used to characterize it.Results: It was observed that on comparison with marker DNA, all samplesof HR regions have almost 500 base pairs identifying HR regions.Conclusion: In this study the identification of HR regions shows thatoccurrence of mutations in HR regions are not enough strong to prevent theirattachment with the primer used.